Healthy Eating: Meals Without Cooking - Karla P. Shelnutt (EDIS, 2011)
Enjoy a word search for the ingredients in this recipe for southwestern black bean salad. This 1-page fact sheet was written by Karla P. Shelnutt and published by the UF Department of Family Youth and Community Sciences, May 2011.